Reactive absorption kinetics of CO2 in alcoholic solutions of MEA: fundamental knowledge for determining effective interfacial mass transfer area - Du Preez, Louis Jacobus (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.